An Island of Amplification in the Ocean of Acceleration - Elena V. Bodrova; Deborah J. Leong (Национальный психологический журнал, 2025)
Background. The idea of amplification of child development as a focus of Early Childhood Education first introduced by L. S. Vygotsky’s colleague A. V. Zaporozhets presents a logical extension of Vygotsky's concept of the Zone of Proximal Development and his principle of instruction leading development. While successfully applied to the design of preschool and kindergarten curricula in Russia, the principle of amplification is still new to Western educators working in the Vygotskian paradigm. Objective. The aim is to discuss the implications of the idea of amplification for Early Childhood Education in the United States and describe the practical implementation of this idea in the «Tools of the Mind» curriculum. Results. With the increasing focus on school readiness in American early childhood education, we found the idea of amplifying development to be a viable alternative to the attempts to accelerate the acquisition of academic skills by transplanting the instructional practices commonly used in elementary grades into a preschool classroom. Based on this idea, we developed a new «Tools of the Mind» curriculum that has been successfully used for 30 years in preschool and kindergarten classrooms across the USA. The cultural-historical approach formed the basis of our curriculum in two ways. First, it comprised the general philosophy of our approach that includes such ideas as the Zone of Proximal Development, learning as appropriation of cultural tools, and make-believe play as the leading activity for preschool-aged children. Second, all of our instructional strategies and materials incorporate one or more specific pedagogical principles derived from the work of Vygotsky and his colleagues and students. Conclusions. Years of research from the cultural-historical perspective have produced particular guidelines on how one should design an ECE curriculum so that it will be aimed at amplifying young children’s development. The empirical evidence we collected in the process of implementing our «Tools of the Mind» curriculum in American preschools and kindergartens demonstrates how a better understanding of these guidelines might have a significant impact on classroom practices across sociocultural contexts.